Spatial heterogeneity of soil acidity properties in peatlands of Western Siberia - Raudina, Tatiana V. (Acta biologica sibirica)
The formation of significant amounts of low molecular weight (LMW) water-soluble organic compounds, which are highly reactive compounds of a non-specific nature, is a feature of the biogeocenoses of the North. Soil acidity, which in turn depends on LMW organic acids content, regulates the migration ability of compounds in landscapes and the bioavailability of nutrients. With an increase in the active layer thickness of peat soils in Western Siberia in the course of climate warming, new portions of LMW water-soluble organic compounds will enter, which will be quickly processed by microorganisms into CH4 and CO2. Five key sites were considered, located within thawed oligotrophic, frozen mound and polygonal bogs. The analysis of zonal patterns of acidity changes in the waters of peat soils indicates an increase in the pH in the series: northern taiga<forest tundra<southern tundra. A feature of the most acidic soils of the northern taiga is the high content of low molecular weight organic acids, the accumulation of which is determined by the species diversity of the vegetation cover and high humidity. The decrease in the content of acids in the soils of the southern tundra is due to changes in climatic conditions and, accordingly, the quality and quantity of organic material involved in the processes of mineralization and humification. Relationships between the pH of the soil solution and such parameters as the specific conductivity, the content of dissolved organic carbon, and the specific UV-absorbency (SUVA245) were revealed. Comparison of the acidity indices of peat soils of the zonal series of the European Northeast with similar ones obtained for the study area of Western Siberia showed that, at the same values of actual acidity, the exchangeable acidity values of peat soils of Western Siberia are slightly lower.